A limitation lifted: A conditional knockdown system reveals essential roles for Polo-like kinase and Aurora kinase 1 in Trypanosoma cruzi cell division - Justin Wiedeman; Ruby Harrison; Ronald Drew Etheridge (Proceedings of the National Academy of Sciences, 2025)
While advances in genome editing technologies have simplified gene disruption in many organisms, the study of essential genes requires development of conditional disruption or knockdown systems that are not available in most organisms. Such is the case for Trypanosoma cruzi , a parasite that causes Chagas disease, a severely neglected tropical disease endemic to Latin America that is often fatal. Our knowledge of the identity of essential genes and their functions in T. cruzi has been severely constrained by historical challenges in very basic genetic manipulation and the absence of RNA interference machinery. Here, we describe the development and use of self-cleaving RNA sequences to conditionally regulate essential gene expression in T. cruzi . Using these tools, we identified essential roles for Polo-like and Aurora kinases in T. cruzi cell division, mirroring their functions in Trypanosoma brucei . Importantly, we demonstrate conditional knockdown of essential genes in intracellular amastigotes, the disease-causing stage of the parasite in its human host. This conditional knockdown system enables the efficient and scalable functional characterization of essential genes in T. cruzi and provides a framework for the development of conditional gene knockdown systems for other nonmodel organisms.